THE IMPACT OF CONSUMPTION OF MORINGA PUDDING ON THE VOLUME AND FREQUENCY OF BREASTFEEDING IN PUBTERMOTHERS - Evy Nurachma, Rosalin Ariefah Putri, Dwi Hendriani, Virdy Kurniawan, Lidia Lushinta (South Eastern European Journal of Public Health, 2025)
Breast milk is the best food for newborn babies and is very important to support the baby's health and development. However, the problem of insufficient breast milk production is still often faced by breastfeeding mothers, especially postpartum mothers. Moringa leaves (Moringa oleifera) have long been known to have various health benefits, one of which is increasing breast milk production. This study aims to analyze the impact of consuming Moringa pudding on the volume and frequency of breastfeeding in postpartum mothers. This research uses a mixed method research method with an experimental approach. The data collection technique in this research is observation and literature study. The collected data was then analyzed to determine the relationship between consumption of Moringa pudding with breast milk volume and frequency of breastfeeding in postpartum mothers. The results of the study showed that postpartum mothers who consumed Moringa pudding experienced a significant increase in the volume and frequency of breast milk compared to those before consuming Moringa pudding. This statement is supported by the statistical results of the MANOVA test showing a significance value of 0.001, which shows that there is a significant positive relationship between consumption of Moringa pudding and breast milk volume and breastfeeding frequency. Therefore, Moringa pudding can be a safe and natural alternative to help postpartum mothers increase breast milk production and meet the baby's nutritional needs.